PROMOSI KESEHATAN TENTANG MEMPERSIAPKAN GENERASI DALAM 1000 HARI PERTAMA KEHIDUPAN PADA IBU HAMIL - Hetty Panggabean; Marni Siregar (Jurnal Mitra Prima, 2020)
ABSTRACT Background Every parent wants their children to grow up healthy. For this reason, mothers and fathers must pay attention to children's nutrition, especially at an important time in their lives, namely, the First Thousand Days of Life (HPK) or what is commonly called the Golden Period. At this time, the mother must meet her daily nutritional intake so that the development of the fetus's organs and brain is perfect. Fulfillment of nutrition for children in the first 1000 days of life is very important. Because if the nutritional intake is not met, the impact on children's development will be permanent. The impact can be in the short term and long term, as a result of malnutrition during fetal period (pregnancy) and early childhood. The short-term impact will interfere with brain development, growth, and metabolic programming. In Simatupang Village, the Muara Community Health Center Work Area, there were 15 pregnant women in October 2018. Based on data obtained in September 2018, it is known that exclusive breastfeeding in the Muara Puskesmas area is still low (37%). Purpose of this PKM activity is to increase public knowledge, especially pregnant women and to determine growth and development in the form of height and weight of toddlers. Method begins with coordination with the Muara Puskesmas, the Village Head, the Simatupang Village Midwife about counseling for pregnant women and examining the growth and development of toddlers. Results Obtained from 15 pregnant women, there were 3 people (20%) who experienced the risk of pregnancy and from the results of the growth and development of underfives including height and weight for 30 toddlers, there were 3 (16.67) toddlers with height and weight. not according to his age. Conclusion Health promotion by conducting counseling and examinations to pregnant women has been carried out. The results of antenatal care found that (20%) had a risk of pregnancy. Examination of height and weight to male and female toddlers found 16.67% experienced height and weight not according to their age. Keywords; The first 1000 days of life, pregnant women